The participation of the muscarinic receptors in the preoptic-anterior hypothalamic areas in the regulation of ovulation depends on the ovary - Adriana Espinosa-Valdez; Angélica Flores; Isabel Arrieta-Cruz; Mario Cárdenas; Roberto Chavira; Roberto Domínguez; María Esther Cruz (BMC, 2016)
Abstract Background Muscarinic receptors (mAChRs) of the preoptic and anterior hypothalamus areas (POA-AHA) regulate ovulation in an asymmetric manner during the estrous cycle. The aims of the present study were to analyze the effects of a temporal blockade of mAChRs on either side of the POA-AHA performed in diestrus-2 rats on ovulation, the levels of estradiol, follicle stimulating hormone (FSH) and luteinizing hormone (LH) and the mechanisms involved in changes in ovulation. Methods Cyclic rats on diestrus-2 day were anesthetized and randomly assigned to the following groups: 1) microinjection of 1 μl of saline or atropine solution (62.5 ng) in the left or right POA-AHA; 2) removal (unilateral ovariectomty, ULO) of the left (L-ULO) or right (R-ULO) ovary, and 3) rats microinjected with atropine into the left or right POA-AHA plus L-ULO or R-ULO. The ovulation rate and the number of ova shed were measured during the predicted estrus, as well as the levels of estradiol, FSH and LH during the predicted proestrus and the effects of injecting synthetic LH-releasing hormone (LHRH) or estradiol benzoate (EB). Results Atropine in the left POA-AHA decreased both the ovulation rate and estradiol and LH levels on the afternoon of proestrus, also LHRH or EB injection restored ovulation. L- or R-ULO resulted in a lower ovulation rate and smaller number of ova shed, and only injection of LHRH restored ovulation. EB injection at diestrus-2 restored ovulation in animals with L-ULO only. The levels of estradiol, FSH and LH in rats with L-ULO were higher than in animals with unilateral laparotomy. In the group microinjected with atropine in the left POA-AHA, ovulation was similar to that in ULO rats. In contrast, atropine in the right POA-AHA of ULO rats blocked ovulation, an action that was restored by either LHRH or EB injection. Conclusions These results indicated that the removal of a single ovary at noon on diestrus-2 day perturbed the neuronal pathways regulating LH secretion, which was mediated by the muscarinic system connecting the right POA-AHA and the ovaries.